Oxidative Stress and Reduced Antioxidative Status, along with Endothelial Dysfunction in Acromegaly - Anagnostis, P.; Efstathiadou, Z. A.; Gougoura, S.; Polyzos, S. A.; Karathanasi, E.; Dritsa, P.; Kita, M.; Koukoulis, G. N. (Hormone and Metabolic Research, 2013)
Acromegaly is characterized by high cardiovascular morbidity and mortality. Oxidative stress and endothelial dysfunction are underlying mechanisms of atherosclerosis.The aim of this study was to evaluate the blood redox status and endothelial function by means of nitric oxide (NO) levels in patients with acromegaly. Total antioxidant capacity (TAC), catalase activity and glutathione concentration (GSH), as measures of antioxidative capacity, total oxidized glutathione (GSSG) and thiobarbituric acid reactive substances (TBARS), as indices of oxidative stress, and NO levels were assessed in 15 patients with acromegaly (age 55.4±10.5 years; 6 males) and 15 age- and sex-matched controls (age 58.4±8.1 years; 7 males). Active disease was present in 12 patients: 11 on current pharmacotherapy and 1 newly diagnosed. Three acromegalics were in remission after successful treatment. Acromegalics as compared with controls had significantly lower levels of catalase activity (8.2±5.8 vs. 51.3±29.1 mmol/ml/min, p<0.001), GSH (0.97±0.54 vs. 1.41±0.35 mmol/l, p=0.006), GSSG (0.27±0.19 vs. 2.04±1.32 mmol/l, p=0.002) and NO levels (6.0±3.1 vs. 43.0±29.8 mmol/l, p<0.001), but higher TBARS (16.3±8.9 vs. 10.1±10.8, nmol/ml, p=0.019). After adjustment for confounders, differences in catalase activity, NO levels and TBARS remained significant (p=0.004, p<0.001 and p=0.025, respectively). No association between IGF-I/GH and oxidative stress markers was noticed, except for a positive correlation between nadir GH and GSSG (r2=0.563, p=0.036). Acromegaly is associated with increased levels of oxidative stress coupled by diminished antioxidant capacity and endothelial dysfunction indicated by the presence of decreased NO levels.
Keywords: acromegaly; oxidative stress; total antioxidant capacity; catalase; glutathione; nitric oxide